Detritivore complex and associated organisms in breeding places of the Rhinoceros beetle, Oryctes Rhinoceros (L.), the key insect pest of coconut - Relox, Richel E. (2003)
Trap boxes filled with coconut wood sawdust utilized as breeding places of the rhinoceros beetle, O. rhinoceros L. were installed in Los Amigos (Davao City), Asuncion, and Sto. Tomas (Davao del Norte) to determine the detritivore species and associated organisms present therein after 3, 6, and 9 months. The susceptibility of detritivores and associated organisms to the green muscardine fungus, Metarhizium anisopliae (Metch.) Sorokin, a biocontrol agent against O. rhinoceros, which is applied on the breeding sites of the beetle, was also assayed. Twenty-six families of detritivores and associated organisms were reckoned, 23 of which belong to Phylum Arthopoda and one each to Phylum Annelida, Phylum Chordata and Phylum Mollusca. In all sites, increase in population of the rhinoceros beetle, detritivores and associated organisms was noted after 6 and 9 months from trap box establishment. On the green muscardine fungus infection trial, while all test O. rhinoceros larvae died, no test detritivore succumbed to infection. The study has shown the diversity of detritivores and associated organisms in coconut wood sawdust and the host-specificity of the M. anisopliae to O. rhinoceros